Femtosecond Stimulated Raman Spectroscopy of Linear Carotenoids - Šímová, Ivana; Chrupková, Petra; Gardiner, Alastair T; Koblížek, Michal; Kloz, Miroslav; Polívka, Tomáš (The journal of physical chemistry letters, 2024)
Femtosecond stimulated Raman spectroscopy (FSRS) and transient absorption data measured in a single experiment are used to determine the vibronic properties of the S1 state of linear carotenoids with different conjugation lengths. The Raman band corresponding to the C═C stretching mode in the S1 state peaks at 1799 cm-1 (neurosporene), 1802 cm-1 (spheroidene), and 1791 cm-1 (lycopene). Contrary to the ground state C═C mode, variation of the C═C stretching mode in the S1 state is small and does not follow a linear dependence on N. The lifetime of the Raman band matches the S1 decays obtained from transient absorption, confirming its S1 state origin. Direct comparison of transient absorption and FSRS signals allowed us to assign Raman signatures of nonrelaxed S1 and S0 states. For lycopene, FSRS data identified a component associated with a downshifted ground state C═C mode, which matches the dynamics of the S* signal observed in transient absorption data.